2005
DOI: 10.1016/j.chemosphere.2005.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A spatial temporal assessment of pollution from PCBs in China

Abstract: This research represents an assessment of the current state of pollution from polychlorinated biphenyls (PCBs) in China. Various environmental media including sediment, water, organism and soil were analyzed and the spatial character of PCB pollution in each environmental medium was determined. On a national basis, PCB levels in all environmental media were relatively low, with little evidence of major contamination in ChinaÕs main regions and rivers. However, there were some locations with high PCB concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
148
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(164 citation statements)
references
References 23 publications
15
148
1
Order By: Relevance
“…The average concentration of 12 dioxin-like PCBs from e-waste recycling sites was 167.7 ng/g dw, which was greater than that from control sites by over 15 times (p < 0.05). The PCBs level was 1-2 orders of magnitude higher than those obtained from some other areas in China, such as Beijing, Shenyang, Wuhan, Hong Kong, and Tibet (14,28), but were at the same level as those found at some heavily polluted sites from China (29,30) and other countries (31,32), though information from China on soil PCB concentration is still very limited up to now. The PCB levels were statistically higher for sampling sites from simple household recycling workshops when compared with samples from large-scale recycling plants (P < 0.05).…”
Section: Resultsmentioning
confidence: 56%
“…The average concentration of 12 dioxin-like PCBs from e-waste recycling sites was 167.7 ng/g dw, which was greater than that from control sites by over 15 times (p < 0.05). The PCBs level was 1-2 orders of magnitude higher than those obtained from some other areas in China, such as Beijing, Shenyang, Wuhan, Hong Kong, and Tibet (14,28), but were at the same level as those found at some heavily polluted sites from China (29,30) and other countries (31,32), though information from China on soil PCB concentration is still very limited up to now. The PCB levels were statistically higher for sampling sites from simple household recycling workshops when compared with samples from large-scale recycling plants (P < 0.05).…”
Section: Resultsmentioning
confidence: 56%
“…The generally low PCB concentrations in the main stream of the Yangtze River could be expected. The results reflect the high dilution of these persistent organic compounds within the TGR as well as the ban of these compounds from production in China since 1974 (Xing et al 2005). At least for the sampling site of this study, no PCB point-source was indicated by the results.…”
Section: Pcb Analysissupporting
confidence: 49%
“…Within the TGR, PCBs have been reported to originate from floods, heavy rains, industrial wastewater, and domestic sewage (Yang et al 2009). Higher PCB concentrations, however, could be observed in eastern China and the lower Yangtze Reaches (Xing et al 2005;Zhang et al 2011) where most of the PCB applications in industry have been located. With tri-and tetra-PCBs being the most abundant PCB congeners in our study, the results are in well accordance to the major produced and applied PCBs in China (Yang et al 2009).…”
Section: Pcb Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…The historically small volume of production and consumption on PCBs in China are probably responsible for this case (Xing et al, 2005). PBDE level in our study were in the same range as those of North America, but were generally higher than those of Europe Eens et al, 2013) (Table S2 in Supplementary Data).…”
Section: Comparison With Other Areasmentioning
confidence: 50%